Burns and prevention: the concern of society raised on websites (Research, Society and Development, 2018)
Burns are very common in Brazilian interiors. Despite the legislation there is an increase in the amount of fires in the country. The purpose of this article is to introduce and discuss braziliam common sense about burns raised on web. An exploratory, qualitative, qualitative research is carried out with a quantitative bias in which the initial notions of common sense about the burnings verified in the Web are searched. It is possible to believe that the burnings are poorly seen by the people in general by the young people, but the people it is a practice widely used as a form of cleaning and prepares land and land for planting.